2020
DOI: 10.35691/jbm.0202.0122
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Nurses About Palliative Care

Abstract: Palliative care enhances the quality of life. To improve the quality of life, it is necessary for nurses to have good knowledge and attitude towards palliative care. It is imperative that nurses provide quality care to terminally ill and chronically sick patients. The present study was designed to assess the knowledge and attitude of medical staff nurses about palliative care in cancer. This cross-sectional, descriptive study was conducted in Mayo Hospital, Lahore and Jinnah Hospital, Lahore with sample size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 3 publications
5
8
0
Order By: Relevance
“…In this systematic review and meta-analysis, the pooled prevalence of the level of nurses' knowledge about palliative care in Ethiopia was 45.57% (95% CI: 35.27–55.87). This finding is almost similar to those in studies conducted in Pakistan (43.5%) [ 11 ], Greece (44.5%) [ 9 ], South Korea (48.3%) [ 29 ], Mongolia (40%) [ 10 ], Iran (39.3%) [ 3 ], Manipur (38%) [ 30 ], Saudi Arabia (36.5%) [ 31 ], India (38%) [ 2 ], Sudan (50.9%) [ 32 ], Spain (54%) [ 33 ], and South Iran (37.95%) [ 34 ]. Conversely, it is higher than those in studies done in Udupi district, India (20.5%) [ 35 ], Palestine (20.8%) [ 36 ], and Guwahati city, India (21%) [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this systematic review and meta-analysis, the pooled prevalence of the level of nurses' knowledge about palliative care in Ethiopia was 45.57% (95% CI: 35.27–55.87). This finding is almost similar to those in studies conducted in Pakistan (43.5%) [ 11 ], Greece (44.5%) [ 9 ], South Korea (48.3%) [ 29 ], Mongolia (40%) [ 10 ], Iran (39.3%) [ 3 ], Manipur (38%) [ 30 ], Saudi Arabia (36.5%) [ 31 ], India (38%) [ 2 ], Sudan (50.9%) [ 32 ], Spain (54%) [ 33 ], and South Iran (37.95%) [ 34 ]. Conversely, it is higher than those in studies done in Udupi district, India (20.5%) [ 35 ], Palestine (20.8%) [ 36 ], and Guwahati city, India (21%) [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, a lack of nurses' knowledge regarding palliative care, which might be a lack of education in pain and symptom management and communication about goals of care, can result in a suboptimal and high cost of care [ 7 ]. Different studies revealed that the nurses' level of knowledge about palliative care was 44.5% in New York [ 8 ], 44.5% in Greece [ 9 ], 40% in Mongolia [ 10 ], and 43.5% in Pakistan [ 11 ], which was below the standards of the board [ 12 ]. As previous studies showed, lack of palliative care education, not participating in important aspects of health care, lack of experience, lack of proper training, few specialization units, and poor arrangement of a career ladder for nurses were found to be contributing factors for the poor knowledge of nurses about palliative care [ 8 , 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The attitude towards the principles of palliative care was at the highest level, and the attitude towards family participation in providing palliative care was at the lowest level. Consistent with the results obtained by Kim et al [20], Parveen et al [21], and Zeru et al [22], despite the participants' low level of knowledge of palliative care, the attitude is at a moderate and acceptable level [23].…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, female gender was mentioned as a predictor of the variable of attitude. Although no study has found a relationship between gender and knowledge of and attitudes towards palliative care [20,21,24,30,31,33], female caregivers appear to be more inclined to provide palliative care and end-of-life care. Gender affects the quality of this type of care [34].…”
Section: Discussionmentioning
confidence: 91%
“…Palliative care is an approach to pain management of patients facing a severe illness that enhances the patient's quality of life. It includes any form of medical and nursing care which is planned to decrease the intensity of symptoms (2). Palliative care signi cantly improves the distressing symptoms of patients, especially those with cancer, heart disease, renal disease, and liver disease (3).…”
Section: Introductionmentioning
confidence: 99%